2009
DOI: 10.1002/chem.200900493
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Controlled Hierarchical Assembly of Ternary Supramolecular Networks at the Liquid–Solid Interface

Abstract: Building and networking: Ternary supramolecular networks have been formed by coadsorption of dissimilar ternary building units at the liquid-solid interface. The structural characteristics of the networks undergo distinctive transformations as the building units change from binary to ternary components (see graphic).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…16,22,43,44 The main driving forces for this phenomenon are van der Waals interactions between a guest and the solid substrate surface and van der Waals interactions between a guest and the surrounding host matrix. For the later interactions, shape and size complementarity between the guest and the pore plays a crucial role.…”
Section: Guest-induced Formation Of Hexagonal Star Structurementioning
confidence: 99%
See 2 more Smart Citations
“…16,22,43,44 The main driving forces for this phenomenon are van der Waals interactions between a guest and the solid substrate surface and van der Waals interactions between a guest and the surrounding host matrix. For the later interactions, shape and size complementarity between the guest and the pore plays a crucial role.…”
Section: Guest-induced Formation Of Hexagonal Star Structurementioning
confidence: 99%
“…For this purpose, self-assembly of hexaalkoxy substituted dehydrobenzo [12]annulene derivatives DBA-OCns was investigated at the tetradecane/graphite interface by means of scanning tunneling microscopy (STM). Monolayer structures were significantly influenced by co-adsorbed tetradecane molecules depending on the alkyl chains length (C 13 -C 16 ) of DBA-OCn. However, none of DBA-OCn molecules formed the expected trigonal complexes, indicating that an additional driving force is necessary for the formation of the trigonal complex and its assembly into the h-star structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Molecular recognition plays an important role in the self-assembly of long range ordered supramolecular architectures, especially for multicomponent systems. Strong and highly directional hydrogen bonding or coordination interaction between the metal ion and ligand are generally preferred, [26][27][28][29] however, van der Waals forces could also yield sufficient recognition if carefully engineered. 30,31 For instance, complex three-, even up to four-component 2D crystals can be fabricated using DBA networks as a host.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, apart from simple co-adsorption, it has been well-documented that the addition of guest molecules could overcome the energy loss caused by unoccupied areas, and subsequently form a specific network. [19][20][21][22] Considering that the H 3 TTCA honeycomb network was just linked by hydrogen bonds between -COOH groups, the inclusion of functional guest molecules would cause the rearrangement of the network. Our previous work reported that when H 3 TTCA was co-adsorbed with H 2 Pc, the H 2 Pc molecules tended to break the original H 3 TTCA chicken-wire structures and insert into the H 3 TTCA arrays because of the geometric mismatch of H 2 Pc and the H 3 TTCA pores.…”
mentioning
confidence: 99%